Global burden of colorectal cancer attributable to high fasting plasma glucose from 1990 to 2021 and projection to 2040 - Li, Yuting; Hong, Weiying; Chen, Peiqing; Zhang, Yu (Frontiers in Oncology, 2025)
BackgroundHigh fasting plasma glucose (HFPG) is an established risk factor for colorectal cancer (CRC). This study analyzes global epidemiological patterns and temporal trends of HFPG-attributable CRC burden from 1990 to 2021, with projections to 2040.MethodsUsing Global Burden of Disease 2021 data, we assessed geographical, sex-specific, age-related, and socio-demographic index (SDI) variations in mortality and disability-adjusted life years (DALYs). Joinpoint regression analysis was employed to evaluate the trends and inflection points, and the Bayesian Age-Period-Cohort (BAPC) model was performed to project future burden.ResultsIn 2021, HFPG accounted for 82,421 CRC deaths (95% UI: 42,427–125,402) and 1,750,923 DALYs (95% UI: 900,573–2,657,995) globally - marking substantial increases since 1990. Age-standardized mortality rates (ASMR) and DALY rates (ASDR) showed modest increases during 1990–2021 with an AAPCs of 0.31, but significant decline were identified post-2019, particularly in ASMR (APC = -0.94, p < 0.05). Regionally, the highest burden were noted in high SDI region, Central Europe, Barbados, and Hungary, with China contributing the absolute numbers of CRC deaths and DALYs. The burden was more pronounced among males and the elderly, with a notable emerging trend of rapidly burden increasing among young males, especially in the 30–34 age group. Projections suggest continued declines in global ASMR and ASDR through 2040.ConclusionDespite global increases in HFPG-attributable CRC burden since 1990, recent declining trends (2019 onward) suggest potential progress in burden mitigation. Considering COVID-19 pandemic impacts on healthcare systems, post-2019 trends require cautious interpretation. Further longitudinal studies are essential to validate these trends. Given the significant variations across gender, age, and SDI, targeted interventional strategies should be developed and implemented to effectively manage this disease burden.